Trinitarian soundings in systematic theology - Metzger, Paul Louis (T & T Clark International, 2005)
Trinitarian Soundings in Systematic Theology is a multi-authored exploration of systematic theology from a Trinitarian perspective. Its aim is to show how the doctrine of the Trinity sheds light on other key doctrines-from prolegomena to eschatology and theological ethics. To borrow a phrase from Robert Jenson, the doctrine of the Trinity 'is not a separate puzzle to be solved but the framework within which all theology's puzzles are to be solved'. Given the scarcity of systematic theologies done 'trinitarianly', this collective project suggests a path to follow in the formulation of each part.